EXPERT SYSTEM FOR NUTRITION DEFICIENCY DIAGNOSIS IN HYDROPONIC PLANTS USING CERTAINTY FACTOR METHOD - dian dian; Raja Tama Raja; Maulana Sena (Jurnal Teknik Informatika (Jutif), 2022)
The city is growing rapidly. Many agricultural lands have been turned into new buildings and structures. Space for farming is getting narrower and more expensive. However, technological developments have allowed people to cultivate crops not on land. Even a house without a yard or yard can still channel the hobby of planting. In principle, planting is an activity to provide nutrients for plants. These nutrients consist of various mineral elements needed by plants. However, the amount of this nutrient is only about 10 percent of the plant's needs. The rest of the plants need a lot of water. With this principle, planting can be done using any media other than soil. Origin, the plant's nutritional needs are met. With this principle, we too can get to know hydroponic farming. The method used in this expert system is the Certainty Factor (CF) method. This method provides a diagnosis in the form of certainty or uncertainty of the conditions in the rules used to conclude. The results of testing this method showed as many as 12 nutritional deficiencies were detected with 41 symptoms experienced. So that it can measure the level of nutritional deficiency that occurs. Expert System in Analyzing Hydroponic Plant Nutrient Deficiency Using Certainty Method. The purpose of this system is to create an expert system that is used to diagnose the symptoms of nutritional deficiencies which ultimately obtain a diagnosis and how to overcome it. Making this expert system using the PHP programming language with MySQL database. The test results show that the program still requires development in terms of its hydroponic material with similar developments to the wider domain of nutrient deficiency problems in hydroponic plants.